2005
DOI: 10.1051/0004-6361:20042351
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact excitation of Al XIII: A relativistic approach

Abstract: Abstract.Energy levels, radiative rates, collision strengths, and effective collision strengths for all transitions up to and including the n = 5 levels of Al XIII have been computed in the j j coupling scheme including relativistic effects. All partial waves with angular momentum J ≤ 60 have been included, and resonances have been resolved in a fine energy grid in the threshold region. Collision strengths are tabulated at energies above thresholds in the range 170.0 ≤ E ≤ 300.0 Ryd, and results for effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…The present radiative rates for E1, M1, E2, M2, E3, and M3 multipole transitions are in excellent agreement with those reported by Aggarwal et al (Aggarwal et al , 2005(Aggarwal et al , 2008c to within 2% for most ∆n 0 transitions, but with a few exceptions for M1 transitions as stated in Chen et al (2010). In addition, we have also compared our rates with those in Jitrik & Bunge (2004).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present radiative rates for E1, M1, E2, M2, E3, and M3 multipole transitions are in excellent agreement with those reported by Aggarwal et al (Aggarwal et al , 2005(Aggarwal et al , 2008c to within 2% for most ∆n 0 transitions, but with a few exceptions for M1 transitions as stated in Chen et al (2010). In addition, we have also compared our rates with those in Jitrik & Bunge (2004).…”
Section: Discussionsupporting
confidence: 92%
“…Ballance et al (2002) performed an R-matrix calculation for transitions among the n ≤ 5 levels in Fe 25+ with close attention to both high-energy behavior of collision strength and radiation damping, employing the semirelativistic intermediate coupling frame transformation (ICFT) method. Malespin et al (2011) reported similar DARC calculations to those performed by Aggarwal et al (Aggarwal et al , 2005(Aggarwal et al , 2008c for highly charged H-like ions of Fe-peak elements with nuclear charge number Z = 24−28, but including radiation damping effects. It was confirmed that radiation damping plays a prominent role for certain near-threshold resonances (Ballance et al 2002;Malespin et al 2011).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The details of our calculations have already been given in our earlier paper (Aggarwal et al 2005) and hence are not repeated here. Additionally, results for all transitions except those which are allowed among the degenerate levels remain the same.…”
Section: Collision Strengthsmentioning
confidence: 99%
“…In a recent paper (Aggarwal et al 2005) we reported results for energy levels, radiative rates, collision strengths, and excitation rate coefficients for transitions among the n ≤ 5 levels of Al xiii. Those calculations were a substantial improvement over our earlier results in the LS coupling scheme for the same ion (Aggarwal et al 2001).…”
Section: Introductionmentioning
confidence: 99%